Scanning Photoelectron Spectro‐Microscopy: A Modern Tool for the Study of Materials at the Nanoscale. Issue 19 (21st August 2018) - Zeller, Patrick; Amati, Matteo; Sezen, Hikmet; Scardamaglia, Mattia; Struzzi, Claudia; Bittencourt, Carla; Lantz, Gabriel; Hajlaoui, Mahdi; Papalazarou, Evangelos; Marino, Marsi; Fanetti, Mattia; Ambrosini, Stefano; et al.
Abstract : The advanced properties of modern materials originate from their nanoscale size and shape and from chemical modifications or doping. Special techniques that can measure the chemical state in the nanoscale are required for exploration and understanding the properties of these materials. While X‐ray photoelectron spectroscopy (XPS) can access the necessary chemical information, conventional setups have no spatial resolution. The scanning photoelectron microscope (SPEM) takes in advent the third generation synchrotron radiation facilities and uses a zone plate (ZP) focusing optics that allows spatially resolved XPS measurements in the submicron scale. Several recent examples of investigations of chemically modified or doped nanomaterials are given. The modification of suspended and supported graphene with nitrogen and fluorine is presented as well as the doping dependent position of the Fermi‐level in single GsAs nanowires and the Mott–Hubbard transition in Cr‐doped vanadium oxide. These examples show several peculiar SPEM abilities like a high surface and chemical sensitivity and a submicron spatial resolution proving the capability and importance of this technique to study materials at the nanoscale. Abstract : Modern materials exhibit outstanding properties due to their size and shape in the nanoscale and by chemical modification or doping. Investigations of these materials require special techniques. Here, the capabilities of spatially resolved X‐ray photoelectron spectroscopy (XPS) measurements with the scanning photoelectron microscope (SPEM) are described. The examples illustrate the important features of a SPEM like a high surface and chemical sensitivity and spatial resolution at the nanoscale.